Local tsunami warnings: Perspectives from recent large events. Issue 3 (12th February 2016) - Melgar, Diego; Allen, Richard M.; Riquelme, Sebastian; Geng, Jianghui; Bravo, Francisco; Baez, Juan Carlos; Parra, Hector; Barrientos, Sergio; Fang, Peng; Bock, Yehuda; Bevis, Michael; Caccamise, Dana J.; et al.
Abstract: We demonstrate a flexible strategy for local tsunami warning that relies on regional geodetic and seismic stations. Through retrospective analysis of four recent tsunamigenic events in Japan and Chile, we show that rapid earthquake source information, provided by methodologies developed for earthquake early warning, can be used to generate timely estimates of maximum expected tsunami amplitude with enough accuracy for tsunami warning. We validate the technique by comparing to detailed models of earthquake source and tsunami propagation as well as field surveys of tsunami inundation. Our approach does not require deployment of new geodetic and seismic instrumentation in many subduction zones and could be implemented rapidly by national monitoring and warning agencies. We illustrate the potential impact of our method with a detailed comparison to the actual timeline of events during the recent 2015 Mw 8.3 Illapel, Chile, earthquake and tsunami that prompted the evacuation of 1 million people. Key Points: Local warning within 2–3 min of a large earthquake is possible Rapid source models can be used for warning This method can be used with current infrastructure